A New Strategy for Antidepressant Prescription - Lavergne, Francis; Jay, Therese M. (Frontiers in Neuroscience, 2010)
From our research and literature search we propose an understanding of the mechanism of action of antidepressants (ADs) that should lead to increase efficacy and tolerance. We understand that ADs promote synaptic plasticity and neurogenesis. This promotion is linked with dopamine (DA) stimulation. Literature shows that all ADs (chemical, electroconvulsive therapy, repetitive transcranial magnetic stimulation, sleep deprivation) increase at least one neuromodulator (serotonin, noradrenaline or DA); this article focuses on DA release or turn-over in the frontal cortex. DA increase promotes synaptic plasticity with an inverted U shape dose-response curve. Specific interaction between DA and glutamate relies on DA (D1 receptors) and Glutamate (NMDA) receptors and/or on neurotrophic factors activation. With the understanding that all ADs have a common, final, DArgic stimulation that promotes synaptic plasticity we can predict that: 1) AD efficiency is related to the compound strength for inducing DArgic stimulation. 2) AD efficiency presents a therapeutic window that coincides with the inverted U shape DA response curve. 3) AD delay of action is related to a “synaptogenesis and neurogenesis delay of action”. 4) The minimum efficient dose can be found by starting at a low dosage and increasing up to the patient response. 5) An increased tolerance requires a concomitant prescription of a few ADs, with different or opposite adverse effects, at a very low dose. 6) ADs could improve all diseases with cognitive impairments and synaptic depression by increasing synaptic plasticity and neurogenesis.